Managing Biological Journal Citations: The Use of a BIBTeX Journal Titles and Abbreviations Database in Conjunction with LaTeX Type-Setting. - Xuejun Dong; Anne C. Nyren; Paul E. Nyren; Geoffrey W. Patton; Bob D. Patton (Issues in Science and Technology Librarianship)
We applied a method to automate bibliographic management for biomedical and environmental scientists/professionals using a BIBTeX database of the titles and abbreviations of :387 mostly biological journals. This database is readily usable to meet the requirements for journal title format by many of today's leading scientific publishers. This article also provides links to additional tools and tutorials for using the proposed database. [ABSTRACT FROM AUTHOR]